2014
DOI: 10.1103/physreve.90.022708
|View full text |Cite
|
Sign up to set email alerts
|

Conformational change in cytochrome P450 reductase adsorbed at a Au(110)—phosphate buffer interface induced by interaction with nicotinamide adenine dinucleotide phosphate

Abstract: Changes observed in the reflection anisotropy spectroscopy (RAS) profiles of monolayers of cytochrome P450 reductase adsorbed at Au(110)-electrolyte interfaces at 0.056 V following the addition of nicotinamide adenine dinucleotide phosphate (NADP(+)) are explained in terms of a simple model as arising from changes in the orientation of an isoalloxazine ring located in the flavin mononucleotide binding domain of the protein. The model also accounts for the changes observed in the RAS as the potential applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…To more fully understand the relationship between protein domain dynamics and CPR turnover, a description of conformational change during enzyme catalysis is required. In recent years, biophysical methods for studying dynamics relevant to catalysis have been developed for CPR and other members of the di‐flavin oxidoreductase family . In selected cases, these have been extended to identify trigger(s) (e.g.…”
Section: Correlating Dynamics With the Enzyme Reaction Cyclementioning
confidence: 99%
See 2 more Smart Citations
“…To more fully understand the relationship between protein domain dynamics and CPR turnover, a description of conformational change during enzyme catalysis is required. In recent years, biophysical methods for studying dynamics relevant to catalysis have been developed for CPR and other members of the di‐flavin oxidoreductase family . In selected cases, these have been extended to identify trigger(s) (e.g.…”
Section: Correlating Dynamics With the Enzyme Reaction Cyclementioning
confidence: 99%
“…Reflective anisotropy spectroscopy (RAS) is a ‘real‐time’ method that has been used to access the conformational landscape of CPR (Fig. A) . RAS is used to measure the difference in normal‐incidence reflectance for two different linear polarization directions , and has been used in recent years to monitor a conformational change in the number of complex redox enzymes that have been immobilized on gold electrodes .…”
Section: Correlating Dynamics With the Enzyme Reaction Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple spectroscopic techniques, including mass spectrometry , NMR , small‐angle X‐ray scattering , neutron scattering and reflection anisotropy , as well as construction of an ‘open’ yeast/human chimeric protein , have been used to demonstrate that CPR exists as a mixture of ‘open’ and ‘closed’ conformations, with long and short flavin–flavin distances, respectively. Moreover, pulsed electron–electron double resonance (PELDOR) spectroscopy measurements of two‐electron‐reduced (di‐semiquinone) forms of several diflavin oxidoreductases has shown that their conformational landscapes are ‘rugged’, with multiple conformers present .…”
Section: Introductionmentioning
confidence: 99%